2012
DOI: 10.1371/journal.pone.0040164
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 Promotes Metabolic Homeostasis via White Adipose and Leptin in Mice

Abstract: Fibroblast growth factor 21 (FGF21) is a potent metabolic regulator, and pharmacological administration elicits glucose and lipid lowering responses in mammals. To delineate if adipose tissue is the predominant organ responsible for anti-diabetic effects of FGF21, we treated mice with reduced body fat (lipodystrophy mice with adipose specific expression of active sterol regulatory element binding protein 1c; Tg) with recombinant murine FGF21 (rmuFGF21). Unlike wildtype (WT) mice, Tg mice were refractory to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
111
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(125 citation statements)
references
References 28 publications
11
111
1
Order By: Relevance
“…The beneficial effects of FGF21 on glucose metabolism and body weight have identified it as a central player in regulating metabolic processes, and adipose tissue is required for its antidiabetic actions (32,33,63). These findings show that FGF21 signaling is modulated by Rev-erb␣ in WAT, not by altering FGF21 levels but through the regulation of its co-receptor KLB in WAT but not in liver.…”
Section: Discussionmentioning
confidence: 89%
“…The beneficial effects of FGF21 on glucose metabolism and body weight have identified it as a central player in regulating metabolic processes, and adipose tissue is required for its antidiabetic actions (32,33,63). These findings show that FGF21 signaling is modulated by Rev-erb␣ in WAT, not by altering FGF21 levels but through the regulation of its co-receptor KLB in WAT but not in liver.…”
Section: Discussionmentioning
confidence: 89%
“…Fibroblast growth factor (FGF)21, a metabolic hormone predominantly produced by liver, has many functional similarities to adiponectin in regulating glucose and lipid metabolism and insulin sensitivity (33)(34)(35)(36)(37). FGF21 acts through a cell-surface receptor composed of a canonical FGF receptor (FGFR) associated with a coreceptor, b-Klotho (KLB) (36)(37)(38).…”
mentioning
confidence: 99%
“…Pharmacologic FGF21 treatment counteracts obesity and its related metabolic disorders including dyslipidemia, glucose intolerance, and insulin resistance (39). In white adipose tissue (WAT), a main target of FGF21 actions, FGF21 stimulates glucoses uptake, modulates lipolysis, and enhances adiponectin expression and secretion (34)(35)(36)(37)39,40). FGF21 also acts directly in the hypothalamus to modulate energy balance and insulin sensitivity (41,42).…”
mentioning
confidence: 99%
“…Systemic administration and overexpression of FGF21 was shown to reduce diet induced as well as genetic obesity, and FGF21 is now considered to have promising therapeutic potential (Ohta and Itoh 2014). By studying lipodystrophic mice (Veniant et al 2012) or mice with fatspecific deletion of the FGF receptor FGFR1 (Adams et al 2012), it was shown that adipose tissue is the key tissue for the majority of the FGF21-dependent metabolic effects by binding of FGF21 to the FGFR1-KLB complex (Luo and McKeehan 2013). The high-fat-diet-induced increase in FGF21 is thought to be linked to a FGF21 resistance as evident by an attenuation of FGF21 effects on liver and adipocytes (Fisher et al 2010).…”
Section: Discussionmentioning
confidence: 99%